Daily habits and kidney stones development rate. Literature review - Iwańczuk, Paweł (Journal of Education, Health and Sport, 2024)
Introduction: Kidney stones disease is a medical condition when hard deposites made of various minerals and substances form inside kidneys. It may lead to clinical symptoms as severe pain felt in the belly area or side of the back. Also it can radiate and reach testicles, groin area, labia. Other symptoms may include blood in the urine, abnormal color of urine, fever, nausea, vomiting. Because of growing incidence rate- adequate question is how can we protect ourselves from kidney stones development by changing habits. Aim of study: Fundamental aim of study is to demonstrate how daily, routine habits changes may have a huge impact on kidney stones development risk. State of knowledge: There are a lot of confirmed parameters and factors which can lead to kidney stones devolopment. Factors that increase risk of developing kidney stones include: dehydration, diet (meat intake, fruit/vegetables intake, sodium intake), family or personal history, obesity, digestive diseases and surgery, metabolic disorders, urinary track infections, anatomical abnormalities- obstruction of the kidney, calyceal diverticulum, horseshoe kidney, ureterocele. This group includes many modified factors, so lifetime risk of kidney stones depends also on our habits and way of life. Conclusion: There are many modified factors which may lead to this disease and because of that it is crucial to improve patients and whole society awareness about them. By appropriate daily habits changes we can significantly reduce risk of lifetime kidney stone disease development. It is important to know that concrete reports and analyses were made and they demonstrated scientifically proven correlations.